A study on spending behaviour of national higher education fund corporation (PTPTN) borrowers / Abdul Rasyid Muhammad Alwi - Muhammad Alwi, Abdul Rasyid (2019)
This study is conducted is to investigate whether there are significant differences in spending behaviours of PTPTN borrowers if they grouped by their profiles. In this study also want to identify the money that their received and percentage of the money they spend in term of food, education needs, personal necessities and transportation. This is to evaluate whether they loose spending or tight spending on all that four items. The data that had been collected will be analyzed using Statistical Package for the social Science (SPSS). Based on the result, all the variable that had been used have significant difference with respondent spending behaviour. They shows that they spent most of their money on food and followed by personal necessities, education needs and transportation expenses. The respondents also have tight spending level on food, personal necessities and transportation but loose spending level on education needs. This shows that the respondents have controllable spending behaviour.